2010
DOI: 10.1111/j.1365-2648.2010.05410.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patient coping preferences on quality of life following renal transplantation

Abstract: Assessment of coping strategies among the transplant population should be further explored in clinical practice, and steps employed to promote the use of positive coping strategies in order to maximize quality of life after transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
2
15
0
2
Order By: Relevance
“…Of all KTRs, 39% [95% confidence interval (CI) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] were severely fatigued. This percentage was significantly higher than in the matched control group (22%, 95% CI 16-28, P = 0.001).…”
Section: Prevalence and Impact Of Severe Fatiguementioning
confidence: 99%
“…Of all KTRs, 39% [95% confidence interval (CI) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] were severely fatigued. This percentage was significantly higher than in the matched control group (22%, 95% CI 16-28, P = 0.001).…”
Section: Prevalence and Impact Of Severe Fatiguementioning
confidence: 99%
“…The patients who can actively influence their own treatment perceive the quality of life as better than the patients who are passive [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in contrast to that of a previous study, which did not find any significant relation between creatinine level and quality of life parameters. 28 Immuno suppressive therapy is an essential part of management of kidney transplant recipients. In addition to the economic burden on patients, immunosuppressant therapy is often associated with severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Giara and associates also reported that avoidance coping strategies may adversely affect both physical and psychological health of kidney transplant recipients. 28 The present study underlines the importance of identifying transplant recipients with negative coping strategies, as these could significantly impair their capacity to handle their illness and treatment appropriately. Furthermore, our findings indicate the importance of individualized counseling programs conducted by care providers of transplant recipients, in order that these patients develop appropriate coping mechanisms.…”
Section: Wenxin Zhang Et Al/experimental and Clinical Transplantationmentioning
confidence: 99%